2018
DOI: 10.1016/j.bbmt.2018.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Utility and Safety of Liver Biopsy in Patients with Undetermined Liver Blood Test Anomalies after Allogeneic Hematopoietic Stem Cell Transplantation: A Monocentric Retrospective Cohort Study

Abstract: Liver blood test anomalies are common after allogeneic hematopoietic stem cell transplantation (allo-HSCT), but their cause often remains difficult to identify. Our objective was to evaluate the safety and utility of liver biopsies in patients who underwent allo-HSCT. In a retrospective single-center cohort study, we reviewed all cases of patients who underwent liver biopsy between June 2005 and July 2017. During this period, 54 biopsies were performed in 45 patients, in which 38 patients underwent allo-HSCT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…VOD/SOS is commonly characterized by hepatomegaly or right upper-quadrant pain, ascites, weight gain, and hyperbilirubinemia [7,8]. Traditionally, the Baltimore or modified Seattle criteria have been used to diagnose VOD/SOS [8][9][10][11][12]. Use of the Baltimore criteria requires the presence of Biology of Blood and Marrow Transplantation journal homepage : www.bbmt.org hyperbilirubinemia (bilirubin 2 mg/dL) for diagnosis, whereas use of the modified Seattle criteria hyperbilirubinemia does not.…”
Section: Introductionmentioning
confidence: 99%
“…VOD/SOS is commonly characterized by hepatomegaly or right upper-quadrant pain, ascites, weight gain, and hyperbilirubinemia [7,8]. Traditionally, the Baltimore or modified Seattle criteria have been used to diagnose VOD/SOS [8][9][10][11][12]. Use of the Baltimore criteria requires the presence of Biology of Blood and Marrow Transplantation journal homepage : www.bbmt.org hyperbilirubinemia (bilirubin 2 mg/dL) for diagnosis, whereas use of the modified Seattle criteria hyperbilirubinemia does not.…”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed a different diagnosis than the one hypothesized before liver biopsy in half of the cases and liver biopsy led to change in management in 49% of cases. In an another study evaluating liver biopsy results, the correlation between pre‐ and post‐liver biopsy diagnosis was noted in 34% of cases and treatment modification was made in 65% of cases following liver biopsy . Few other studies have reported treatment modifications in 37% to 66% of cases following liver biopsy .…”
Section: Discussionmentioning
confidence: 91%
“…In particular, the decision to perform a liver biopsy should be considered carefully, as the procedure carries a small risk of serious and potentially life-threatening complications. In fact, in a more recent study, the need to perform a liver biopsy to confirm VOD/SOS was very low (45 of 1472 patients; 2.8%) [53]; however, that study also showed that no patient developed complications related to the biopsy procedure, and that the biopsy results influenced patient management in 65% of the cases. If liver biopsy is required in the early stages after HCT, transjugular biopsy is recommended over percutaneous biopsy owing to the increased risk of hemorrhage associated with the latter approach [21,52].…”
Section: Liver Biopsymentioning
confidence: 94%